2018
DOI: 10.1093/pch/pxy018
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of early-onset neonatal sepsis in Canada

Abstract: Objective: To determine the incidence, types of organisms and resistance patterns involved in early-onset neonatal sepsis in Canada. Study design: Early-onset neonatal sepsis cases were identified through the Canadian Paediatric Surveillance Program. Neonates were excluded if they were asymptomatic or if intracranial procedures preceded a positive cerebrospinal fluid culture. Results: One hundred and twenty-seven cases were identified (0.17 cases per 1000 live births). Group B Streptococcus accounted for 41.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
(94 reference statements)
0
5
0
1
Order By: Relevance
“…Importantly, these estimates remain high when compared to those in high income countries. For instance, the incidence of early onset cSBI is ten times higher when compared to those in North America (0.17 to 1 per 1,000 live births) [ 12 14 ]. In LMICs, recent studies are scare, but available ones from Asia and Sub-Saharan Africa showed slightly lower incidence of cSBI when compared to results of BIRDY 2 (estimated incidence in Bangladesh (one month follow-up): 3.0, in India (two months follow-up): 6.7 and in Kenya (two months of follow-up): 5.5 cSBI per 1,000 live births) [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these estimates remain high when compared to those in high income countries. For instance, the incidence of early onset cSBI is ten times higher when compared to those in North America (0.17 to 1 per 1,000 live births) [ 12 14 ]. In LMICs, recent studies are scare, but available ones from Asia and Sub-Saharan Africa showed slightly lower incidence of cSBI when compared to results of BIRDY 2 (estimated incidence in Bangladesh (one month follow-up): 3.0, in India (two months follow-up): 6.7 and in Kenya (two months of follow-up): 5.5 cSBI per 1,000 live births) [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, late-onset neonatal sepsis (LONS) develops three days after birth, with Staphylococcus spp. being the most often observed pathogens [13] . This cross-sectional study was carried out at NICU of Kasr Al-Ainy Hospital, Cairo University, Egypt, from Janurary 2018 to August 2018.…”
Section: Discussionmentioning
confidence: 99%
“…En Canadá se logró demostrar que la rotura prematura de membranas prolongado ocurre en las 26 semanas de gestación debido a infecciones vaginales por las bacterias de Escherichia coli y Estreptococo del grupo B donde se asocia a una sepsis neonatal, los síntomas más frecuentes que se muestra es un peso al nacer es menor de 2000 g, dificultad respiratoria, vómito, letargia e inestabilidad térmica, además las características para un diagnóstico son un hemocultivo, hemograma, VSG y la proteína C reactiva (Sgro et al, 2019).…”
Section: Introductionunclassified